Rabies in wild animals: Risks to public health (Research, Society and Development, 2025)
Rabies is an acute and lethal viral zoonosis caused by viruses of the Lyssavirus genus, posing a threat to public health, especially when associated with wild animals. Brazil has made progress in controlling urban rabies; however, sylvatic rabies has become an increasing challenge. Between 2010 and 2024, more than 60% of human cases were attributed to wild animals, such as hematophagous bats and primates. Given this context, the study aims to analyze the risks associated with rabies in wild animals and its implications for public health. This study, qualitative in nature and based on a literature review methodology, aims to analyze the risks of rabies in wild animals and its implications for public health. Scientific publications and official documents on rabies epidemiology, zoonoses, and environmental surveillance were examined. The results indicate that virus circulation among wild species, such as bats and marmosets, represents a serious risk, particularly in areas with limited sanitary surveillance. The detection of viral variants shared among different species highlights an increasing complexity in the transmission chain. It is concluded that prevention should include health education, vaccination of domestic animals, environmental monitoring, and integration between public health and environmental conservation. The study underscores the importance of effective and cross-sectoral public policies to reduce risks to human health. The project proved economically feasible by using online resources and home-based infrastructure.